Potentiometric determination of alendronate in pharmaceutical formulations - De Haro Moreno, Andréia [UNESP]; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP] (My University, 2004)
A simple, precise, fast and low-cost potentiometric method for alendronate determination in pharmaceutical formulations has been proposed. Alendronate present in tablets at the known concentration was potentiometrically titrated in an aqueous solution using a combined glass electrode coupled with an autotitrator. Determination limit of alendronate was 20.0 μg mL-1. In the presence of common excipients, such as lactose, microcrystalline cellulose, glucose, croscarmellose sodium, starch, talc, magnesium stearate and titanium dioxide no interferences were observed. The method proposed was validated by determining alendronate in various dosage forms. The average RSD was 0.75%.
Keywords: Alendronate; Pharmaceutical formulations; Potentiometric determination